2010
DOI: 10.4238/vol9-2gmr826
|View full text |Cite
|
Sign up to set email alerts
|

The azoospermia factor locus-c region was found to be related to Klinefelter syndrome in Turkish patients

Abstract: ABSTRACT. We looked for a possible association between Klinefelter syndrome (KFS) and microdeletions in the Y chromosome in Turkish KFS patients. We examined the frequency of KFS in male patients with proven non-obstructive azoospermia and the types of Y chromosome microdeletions in these KFS patients. Fifty azoospermic patients and 50 fertile men were included in this study. KFS was found in 14 azoospermic patients. Y chromosome microdeletions were found in eight KFS patients. Azoospermia factor locus c (AZFc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Other studies reported Y chromosome microdeletions in patients with KFS; Mitra et al (2006) found that 4 of 14 KFS patients (18 STSs) showed microdeletions, including 3 cases with the AZFa deletion and 1 with the AZFb deletion. Ceylan et al (2010) found that 8 of 14 Turkish KFS patients (6 STSs) had AZFc deletions, while no deletion was detected in the control group. Hadjkacem-Loukil et al (2009) found that 6 of 9 KFS patients (19 STSs) showed AZF deletions, including a gr/gr deletion, indicating that partial deletion of AZFc may not play a role in susceptibility to KFS.…”
Section: Discussionmentioning
confidence: 93%
“…Other studies reported Y chromosome microdeletions in patients with KFS; Mitra et al (2006) found that 4 of 14 KFS patients (18 STSs) showed microdeletions, including 3 cases with the AZFa deletion and 1 with the AZFb deletion. Ceylan et al (2010) found that 8 of 14 Turkish KFS patients (6 STSs) had AZFc deletions, while no deletion was detected in the control group. Hadjkacem-Loukil et al (2009) found that 6 of 9 KFS patients (19 STSs) showed AZF deletions, including a gr/gr deletion, indicating that partial deletion of AZFc may not play a role in susceptibility to KFS.…”
Section: Discussionmentioning
confidence: 93%
“…There have been several conflicting reports about the association between KFS and AZF microdeletions (Ambasudhan et al, 2003;Ferrás et al, 2004;Foresta et al, 2005;Mitra et al, 2006;Arruda et al, 2007;Choe et al, 2007;Ceylan et al, 2010;Behulova et al, 2011). Accordingly, analysis and comparison with other studies of these associations is justified.…”
Section: Discussionmentioning
confidence: 99%
“…Microdeletions of the Y chromosome are the second most common cause of spermatogenic failure after KFS (Ceylan et al, 2010;Behulova et al, 2011). However, the frequency of AZF microdeletions in azoospermic males varies considerably across studies and populations (3-55%) (Foresta et al, 1998;Ambasudhan et al, 2003;Vogt et al, 2004;Behulova et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations